Lsa inscripciones de nacimiento igualitarias - Pszemiarower, Damián Jonatan (2015)
Family structures are permanently changing. Family law evolves with the appearance of new challenges. An issue that has recently appeared as a new matter is the registration of children?s birth in gay, lesbian and bisexual families. The legal tools which have been developed about this point are presented here